Fluidic behaviours in a 2D folded-graphene aerogel monolith. (29th September 2015) - Xu, Xiang; Zhang, Qiangqiang; Yu, Yikang; Yang, Kaichun; He, Qiuyu; Chen, Weizhe; Li, Hui; Qiao, Yu
Abstract: Conduction of pressurized water through two-dimensional (2D) layers in monolithic folded-graphene aerogels (FGA) is investigated experimentally. The synthesized FGA has a regular layered structure with a uniform d -spacing around 20 nm. Compared with one-dimensional nanofluidics in carbon nanotube arrays that have a similar characteristic length scale, the conduction pressure of FGA is much lower by nearly 2/3. The reduction in pressure may be attributed to the more energetically favourable molecular configurations in the 2D nanoenvironment, associated with the relaxation of lateral constraints of water molecules. The water conduction pressure through FGA rises exponentially with the sample thickness, due to the interlayer resistance. This finding may find wide applications in nanotransportation, nanofiltration, and nanofluidic energy management.